Biography—Art—Identity: About the Silesian Project of Anna and Franciszek Seifert and Their Relationship with Andrzej Bobkowski - Nowak, Maciej (Porównania, 2022)
The article reveals the possibilities of the biography method as a valuable interpretive tool within the humanities. It discusses the life of a Polish writer Andrzej Bobkowski and his relationships with an artistic couple Anna and Franciszek Seifert. The paper discusses the aesthetic message of murals made by the Seiferts for the "Robur" company and their associations with Bobkowski’s views expressed in his works. Topics include Bobkowski’s and the Seiferts’ relation to the Silesia region, the artistic duo's role as mentors to the young writer, and their impact on his life.